Information Technology Governance In The Malaysian Electronics Manufacturing Industry - Teo, Wil Ly (2007)
A surprising research finding is that organisations with growth as their primary goal showed marginally higher IT governance performance, contrary to espected outcomes. This finding indicates that the understanding and implementation of IT governance is on track, though familiarity with technicalities of the frameworks should be improved.